MODEL PENGADAAN BAHAN BAKU KURMA SALAK MENGGUNAKAN TEKNIK LOT for LOT - Imam Gazali; Moh Fuad FM; Banun Diyah Probowati (AGROINTEK, 2015)
The raw material is absolutely a need for a company to smooth production process. Procurement of raw materials is a major factor in the production process activities. One measure of the performance of control of raw material procurement is to minimize the cost. This study was conducted to determine and specify in providing a more economical raw materials between methods of this industry and Lot for Lot Technical of Material Requirement Planning. Calculation of the total cost of raw material requirement by considering the cost of purchase and cost of ordering. The data used to calculate the total cost of procurement of products obtained from the data demand of snake fruits are translated based on the structure of the product to determine the need for raw materials. Material Requirement Planning Methods with Lot for Lot technical generate total procurement costs are lower than the method of this industry. The total cost of procurement by the method of the company amounted to Rp 5,396,000.00 and Rp 5,331,600.00 of lot for lot. The savings that can be generated by lot for lot is Rp.160.400 or 2.97%. Based on the results of the calculations are more economical method to be applied in industry with Lot for Lot.